Kajian Potensi Masjid sebagai Pendukung Kepariwisataan Halal di Kota Sabang, Aceh - Pratitou Arafat; Meilya Silvalila; Siswani Sari; Naufal Fariq (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to map and analyze the potential of mosques as a halal tourism component in Sabang. Regarding halal tourism,mosques in Sabang can be seen from two perspectives: as supporting infrastructure for halal tourism or as tourist objects. The methods used in this research are spatial analysis, surveys, and field observations of all mosques in Sabang in order to assess the mosque potential in the halal tourism scheme by analyzing several factors, which are the proximity of mosques to popular tourist destinations, the historical value of mosques,